Growth of "nanica" banana under different qualities of irrigation water - dos Santos, José Geraldo Rodrigues; Gheyi, Hans Raj (Pesquisa Agropecuaria Brasileira, 1993)
Effects of two types of water (predominantly chlorinated and bicarbonated) and four different salinity levels (2, 10, 25 and 40 meq/l) during first five mouths of growth of "Nanica" banana (Musa sp.) were studied. The experiment was conducted in a greenhouse using an alluvial eutrophic soil and a completely randomized 2 x 4 factorial design with four replications. The irrigation waters of different salinity levels were prepared by adding adequate volumes of NaHCO3, CaCl2, MgCl2 and NaCl in water used for control treatment (2 meq/l) maintaining proportion Na:Ca:Mg as 7:1.5:1.5 and Cl arid HCO3 ratio 7:3 or vice-versa. The plants irrigated with such waters showed significant decreases in height, diameter of pseudostem, leaf area and dry weights of stalk and roots; however, drastic effects were observed in treatments with salinity levels of 25 meq/l and above. The reductions were found to be more accentuated for leaf area and dry weights irrespectively of type of water. Further, the study of leaf elongation showed that increase in water salinity besides provoking reductions in leaf area delayed upto eight days in complete unrolling of leaf.